2022
DOI: 10.3390/ani12111357
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Contagious Yawning in Juvenile Ravens (Corvus corax): An Observational Study

Abstract: The overt and reflexive matching of behaviors among conspecifics has been observed in a growing number of social vertebrates, including avian species. In general, behavioral contagion—such as the spread of yawning—may serve important functions in group synchronization and vigilance behavior. Here, we performed an exploratory study to investigate yawn contagion among 10 captive juvenile ravens (Corvus corax), across two groups. Using observational methods, we also examined the contagiousness of three other dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…A further important feature linking yawning to social environment is the susceptibility to respond to conspecifics’ yawn with another yawn (yawn contagion) (Provine 2005 ). Yawn contagion has been extensively documented in human (Norscia and Palagi 2011 ; Palagi et al 2020 ; Provine and Hamernik, 1986 ; Provine, 2005 ) and nonhuman animals (birds, Miller et al 2012 ; social carnivores, Romero et al 2014 ; Casetta et al 2021 ; Ake and Kutsukake 2023 ; monkeys, Palagi et al 2009 ; Valdivieso-Cortadella et al 2023 ; great apes, Campbell and Cox 2019 ; Demuru and Palagi 2012 ) with some exceptions (birds, Gallup et al 2022 ; lowland gorillas, Palagi et al 2019a , b ). It has been recently demonstrated that yawn contagion can also occur between different species (Gallup and Wozny 2022 ; Pedruzzi et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A further important feature linking yawning to social environment is the susceptibility to respond to conspecifics’ yawn with another yawn (yawn contagion) (Provine 2005 ). Yawn contagion has been extensively documented in human (Norscia and Palagi 2011 ; Palagi et al 2020 ; Provine and Hamernik, 1986 ; Provine, 2005 ) and nonhuman animals (birds, Miller et al 2012 ; social carnivores, Romero et al 2014 ; Casetta et al 2021 ; Ake and Kutsukake 2023 ; monkeys, Palagi et al 2009 ; Valdivieso-Cortadella et al 2023 ; great apes, Campbell and Cox 2019 ; Demuru and Palagi 2012 ) with some exceptions (birds, Gallup et al 2022 ; lowland gorillas, Palagi et al 2019a , b ). It has been recently demonstrated that yawn contagion can also occur between different species (Gallup and Wozny 2022 ; Pedruzzi et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the reflexive tendency to yawn following the detection of yawns in others, i.e., contagious yawning, is a well-documented phenomenon that may serve to enhance vigilance and synchronization in groups [ 19 ]. Distinct from physiologically triggered yawns, which are ubiquitous in vertebrates, there is a great deal of variation across species when it comes to the tendency to yawn contagiously [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, budgerigars have been shown to yawn in response to both live demonstrators and visually recorded conspecifics [ 43 , 44 ]. However, a recent study found no evidence for contagious yawning among juvenile ravens [ 23 ].…”
Section: Introductionmentioning
confidence: 99%